xCT as a potential marker for neuroendocrine cells in high-risk prostate cancer and the relation to AL122023.1-miR-26a/30d/30e axis - Elena D. Wilhelm; Jaroslaw T. Dankert; Marc Wiesehöfer; Sven Wach; Mathias Wagner; Martin Spahn; Marianna Kruithof-de Julio; Gunther Wennemuth (PLoS ONE, 2025)
Prostate cancer is the second most common type of cancer in male worldwide. Stromal-epithelial interaction is thought to have a major impact on cancer development and progression. Previous studies have shown that interaction via soluble factors lead to a reduction in the expression of xCT and AL122023.1 in the prostate carcinoma cell line LNCaP after seven days of co-culture with primary stromal p21 cells. In this study, we validated the repression of xCT and AL122023.1 at RNA level using quantitative real-time PCR and at protein level by Western Blotting. Furthermore, xCT is known to be a putative target for miRNAs miR-26a, miR-30d and miR-30e, which in turn potentially interact with AL122023.1. The lncRNA-miRNA-interaction was verified by luciferase reporter assays. However, miR-26a/-30d/-30e did not inhibit xCT expression at protein level. Nevertheless, indirect inhibitory effect of AL122023.1 on the xCT expression could be shown. Moreover, immunostaining revealed precise xCT expression in neuroendocrine cells, ranging from fetal, healthy juvenile, and adult prostate tissue to benign prostatic hyperplasia and finally advanced prostate cancer. This study explores the relevance and function of xCT and AL122023.1 in the prostate and exposes xCT as a potential marker or therapeutic target in high-risk prostate cancer.